PKCϵ-mediated phosphorylation of TRPC3 channel at S712 is essential for its inactivation during inflammatory signaling - Casas, Javier; Meana, Clara; San-José, Gonzalo; Balsinde, Jesús; Balboa, María A. (Frontiers in Immunology, 2026)
The transient receptor potential canonical 3 (TRPC3) channel plays a pivotal role in macrophage-mediated inflammatory signaling by regulating intracellular calcium dynamics. This study identifies phosphorylation at serine 712 (S712) by protein kinase C ϵ (PKCϵ) as a critical mechanism for TRPC3 inactivation. Using HEK-TLR4 cells and THP-1 human macrophages, we demonstrate that the S712A-TRPC3 mutant, which cannot be phosphorylated, exhibits altered subcellular localization, promoting persistent calcium influx, and enhanced expression of proinflammatory cytokines such as TNFα and inflammatory mediator enzyme COX2 during LPS cellular activation. Live-cell imaging and FRET assays reveal that PKCϵ, but not other PKC isoforms, translocates to endomembranes upon LPS stimulation and interacts directly with TRPC3. Pharmacological inhibition and gene silencing of PKCϵ mimic the effects of the S712A mutation, confirming its role in terminating TRPC3-mediated calcium signaling. These findings establish PKCϵ-mediated phosphorylation of TRPC3 at S712 as a key regulatory mechanism for resolving inflammatory calcium signaling in macrophages.